A new insight into annealing parameters in tailoring the mechanical properties of a medium Mn steel. (September 2021) - Jing, Songyang; Ding, Hua; Ren, Yuping; Cai, Zhihui
Abstract: Generally, the mechanical properties of medium Mn steels are mainly tailored by adjusting temperature and duration of intercritical annealing (IA). However, in the present study, it is found that the temperature-rise-period in IA also plays a remarkable role in the control of the mechanical properties of the investigated medium Mn steel. A longer temperature-rise-period is conducive to the formation of austenite grains at different temperatures, resulting in more heterogeneous distribution of Mn element within an individual austenite grain and among different austenite grains. This heterogeneous microstructure leads to the difference in the yield strength among austenite laths and a slow strain-induced-martensite-transformation kinetics. Eventually, the yield strength and total elongation of the investigated steel has been significantly increased while high ultimate tensile strength is maintained. This study provides a new insight into comprehensively understanding the role of annealing parameters so as to improve the mechanical properties of medium Mn steels in industrial production. Graphical abstract: Image, graphical abstract